Impact of Rewards System on Employee Motivation: A Study of a Manufacturing Firm in Oman - Noor, Zaha; Nayaz, Nishatnaz; Solanki, Vrushabh; Manoj, Adarsh; Sharma, Arti (International Journal of Business and Management Future, 2020)
This paper illustrates the importance of employee motivation and the influence of reward and recognition program on the motivation and performance of the manufacturing and production workers of a manufacturing firm situated in the Sultanate of Oman. The goal of the report is to depict the predominant effect of reward and recognition on overall productivity, performance, and motivation. The data gathered for the research was through an exploratory research design wherein the survey questionnaire was distributed to a population of 30 respondents through a stratified sampling technique. Both the qualitative and quantitative data were considered while concluding the major findings, followed by proposing suggestions to improve the motivation levels of employees and enhance their rewards and recognition program.